2013
DOI: 10.5296/ajfa.v5i1.3023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deposit Insurance on Risk Taking in Asian Banks

Abstract: This paper uses a panel database of 401 banks in 31 Asian countries over the period from 2000 to 2010 to examine the effects of deposit insurance on banks' risk-taking incentives. We find that risk-taking incentives vary with bank size and risks. In addition, differentiated premiums may not accurately reflect the level of risk that a bank poses. In the presence of a deposit insurance scheme, the pattern of the non-linear relationship between bank size and risk-taking significantly changes. Our results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Contrastingly, some studies explore whether the impact of deposit insurance on bank risk-taking incentives (Enkhbold & Otgonshar, 2013;Karas et al, 2019). Enkhbold & Otgonshar (2013) Other studies apply capital-risk weighted asset ratios to capture bank risk.…”
Section: Previous Literature On Market Discipline and Bank Risk-takingmentioning
confidence: 99%
“…Contrastingly, some studies explore whether the impact of deposit insurance on bank risk-taking incentives (Enkhbold & Otgonshar, 2013;Karas et al, 2019). Enkhbold & Otgonshar (2013) Other studies apply capital-risk weighted asset ratios to capture bank risk.…”
Section: Previous Literature On Market Discipline and Bank Risk-takingmentioning
confidence: 99%
“…Additionally, Enkhbold & Otgonshar (2013) in their research cutting across 31 Asian countries obtained and analysed data from a sample of 401 banks. Findings from the study revealed that banks exhibited increased market discipline arising from the implementation of DIS.…”
Section: H02mentioning
confidence: 99%
“…This study is therefore an attempt to bridge this gap by considering how deposit insurance schemes influence the deposit mobilization potential of deposit money banks in IADI's countries. Enkhbold and Otgonshar (2013) conducted a study on deposit insurance and risk-taking in Asian banks. The risk taken was peroxide by the cost of holding deposit reserves while deposit insurance was measured.…”
Section: Literature Reviewmentioning
confidence: 99%